The Influence of Online Customer Review and Online Customer Rating Mediated by Consumer Trust on Skintific Product Purchase Decisions via Tiktokshop - Kusmawati, Kusmawati; Anggarawati, Sularsih (Universitas Bengkulu, 2024)
The purpose of this study was to examine the influence of Online Customer Reviews and customer ratings mediated by consumer trust on the purchase decisions of Skintific products through TikTok shopping. The sampling technique in this study used purposive sampling techniques. The data collection technique uses questionnaires that are disseminated online through social media. The sample in this study was 287 respondents using Skintific skincare at Tiktokshop in Bengkulu City. The analytical tool used PLS-SEM with the assistance program SmartPls version 3.2.9. The results showed that (1) Online Customer Review and online customer rating have a positive effect on purchasing decisions; (2) customer trust positively influences purchasing decisions; (3) Online Customer Reviews and online customer rating have a positive effect on customer trust (4) customer trust mediates the influence of Online Customer Reviews and online customer rating on purchasing decisions; The practical implication in this research is for Tiktokshop developers to be able to continue to maintain quality and or continue to innovate to develop online customer rating and Online Customer Review features as platform advantages that help consumers before buying a product. Furthermore, for Skintific skincare companies on TikTokshop to be able to maintain product quality so that consumer response to Online Customer Reviews and Online Customer Reviews is good, so it will also result in increased sales of skintfic products